High School Students' Proficiency and Confidence Levels in Displaying Their Understanding of Basic Electrolysis Concepts - Sia, Ding Teng; Treagust, David; Chandrasegaran, Arulsingam (Springer Netherlands, 2012)
This study was conducted with 330 Form 4 (grade 10) students (aged 15 – 16 years) who were involved in a course of instruction on electrolysis concepts. The main purposes of this study were (1) to assess high school chemistry students’ understanding of 19 major principles of electrolysis using a recently developed 2-tier multiple-choice diagnostic instrument, the Electrolysis Diagnostic Instrument (EDI), and (2) to assess students’ confidence levels in displaying their knowledge and understanding of these electrolysis concepts. Analysis of students’ responses to the EDI showed that they displayed very limited understanding of the electrolytic processes involving molten compounds and aqueous solutions of compounds, with a mean score of 6.82 (out of a possible maximum of 17). Students were found to possess content knowledge about several electrolysis processes but did not provide suitable explanations for the changes that had occurred, with less than 45 % of students displaying scientifically acceptable understandings about electrolysis. In addition, students displayed limited confidence about making the correct selections for the items; yet, in 16 of the 17 items, the percentage of students who were confident that they had selected the correct answer to an item was higher than the actual percentage of students who correctly answered the corresponding item. The findings suggest several implications for classroom instruction on the electrolysis topic that need to be addressed in order to facilitate better understanding by students of electrolysis concepts.